2011
DOI: 10.3109/09638288.2010.517897
|View full text |Cite
|
Sign up to set email alerts
|

The impact of stroke-related dysarthria on social participation and implications for rehabilitation

Abstract: The impact of stroke-related dysarthria transcends the physiological impairment to impact upon individuals' social participation, which is key to the process of rehabilitation. The development and evaluation of the effectiveness of an intervention that addresses these impacts is the next challenge for therapists and researchers working in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
99
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(103 citation statements)
references
References 16 publications
2
99
1
1
Order By: Relevance
“…527,531 The effects of motor speech disorders after stroke extend beyond the physiological characteristics of the impairment. Studies have shown that the resulting communication difficulties affect social participation and quality of life 532,533 and that the psychosocial impact of a motor speech disorder is disproportionate to the severity of the physiological impairment. …”
Section: Motor Speech Disorders: Dysarthria and Apraxia Of Speechmentioning
confidence: 99%
“…527,531 The effects of motor speech disorders after stroke extend beyond the physiological characteristics of the impairment. Studies have shown that the resulting communication difficulties affect social participation and quality of life 532,533 and that the psychosocial impact of a motor speech disorder is disproportionate to the severity of the physiological impairment. …”
Section: Motor Speech Disorders: Dysarthria and Apraxia Of Speechmentioning
confidence: 99%
“…These have been described as participation restrictions and are recognized as being influenced not only by the physiologic and perceptual characteristics described above but also by contextual factors, including environmental or personal features. The psychosocial aspects of dysarthria have been examined through personal accounts (Cant, 1997) and using qualitative methods in acquired dysarthria (Brady, Clark, Dickson, Paton, & Barbour, 2011b;Dickson, Barbour, Brady, Clark, & Paton, 2008;Miller, Noble, Jones, & Burn, 2006;. Consensus exists that acquired dysarthria changes the lives of the speakers experiencing it.…”
mentioning
confidence: 99%
“…Consensus exists that acquired dysarthria changes the lives of the speakers experiencing it. Speakers with acquired dysarthria report social isolation (Brady et al, 2011b), feelings of perceived stigmatization (Dickson et al, 2008), and changes in self-identity and social relationships (Brady et al, 2011b). Everyday activities, such as conversation, are difficult even when voice or speech changes are mild and do not interfere with speech intelligibility (Miller et al, 2006).…”
mentioning
confidence: 99%
“…People with dysarthria have reported being conscious of other people's attitudes to their changed speech. 284,285 Listeners were perceived by people with dysarthria to be condescending and to negatively evaluate the person with dysarthria, due to their communication impairment. [284][285][286] The ability to work, and relationships with spouses and friends were reported to be negatively affected by communication and physical impairments.…”
Section: Discussionmentioning
confidence: 99%
“…284,285 Listeners were perceived by people with dysarthria to be condescending and to negatively evaluate the person with dysarthria, due to their communication impairment. [284][285][286] The ability to work, and relationships with spouses and friends were reported to be negatively affected by communication and physical impairments. 285 Feelings of embarrassment, reduced confidence, and inadequacy were reported by the participants with dysarthria.…”
Section: Discussionmentioning
confidence: 99%